Projeto de um sistema de registro de sinais de neurônios em matriz de microeletrodos com ressonância estocástica - Fambrini, Francisco (Universidade Federal de São Carlos, 2019)
This PhD thesis aims at the study and practical implementation of a complete system capable of recording electrical signals from a Microelectrode Array. This multi-electrode planar matrix known as MEA (MicroElectrode Array), is built with the same technology as nanoscale integrated circuits, and allows a biological culture of neural cells to be performed at its center. Through studies on MEAs, we can better understand the pattern of spikes and bursts generated by neurons on in vitro cultures. The electrical signals captured and recorded from microelectrodes have an amplitude of the order of microvolts (µV) and need to be amplified by special circuits, with filters capable of selecting the frequency band of interest. However, often the electrical levels of the signals captured in MEAs are so small that they cannot be amplified by conventional techniques, as they are of the same order as the random noise level produced by the amplifier circuits. Some electrical signals are impossible to record through operational amplifiers conventionally used in electronics. In this paper, we describe the application of the Stochastic Resonance Phenomenon (SR) to record signals of very low intensity compared to conventional amplification methods for signals captured in MEA. Therefore, the work of this thesis consists in the development of the acquisition and recording system of signals from in vitro cultured neurons in MEA, using conventional and SR methods; electrical measurements of the developed bench system and comparison with the values obtained in the simulation, testing conventional amplifiers and SR amplification systems and validation of the entire device in a real experiment with an in vitro culture of neurons, which was performed in an electrophysiology laboratory at the Federal University of Uberlândia. The results of these experiments showed stochastic resonance is useful for detecting signals below 100 µV p-p. For higher amplitude signals, there is no advantage in using the RE as an amplification element due to the distortion produced in the signals.
Design of a registration system for neuron signals in microelectrode array with stocastic resonance
Keywords: Matriz de microeletrodos; Sinais eletrofisiológicos; Culturas de neurônios in vitro; Ressonância Estocástica; Amplificadores; Microelectrode array; Electrophysiological signals; In vitro neuron culture; Stochastic resonance; Amplifiers; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO